2017
DOI: 10.1016/j.bpj.2016.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Optical Trapping Nanometry of Hypermethylated CPG-Island DNA

Abstract: Cytosine methylation is a key mechanism of epigenetic regulation. CpG-dense loci, called "CpG islands", play a particularly important role in modulating gene expression. Methylation has long been suspected to alter the physical properties of DNA, but the full spectrum of the evoked changes is unknown. Here we measured the methylation-induced nanomechanical changes in a DNA molecule with the sequence of a CpG island. For the molecule under tension, contour length, bending rigidity and intrinsic stiffness decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
6
30
0
Order By: Relevance
“…Hypermethylation of CGI commonly induces gene silencing and in some cases this has been attributed to nucleosome stabilization (10). We found that complete hypermethylation of the poly-CG molecule significantly increases its crookedness and flexibility, in quantitative agreement (table S3) with recent optical tweezers experiments reporting both an unusually high and a softening induced by hypermethylation in CGI (23). This could increase nucleosome affinity for a hypermethylated CGI (24).…”
supporting
confidence: 89%
“…Hypermethylation of CGI commonly induces gene silencing and in some cases this has been attributed to nucleosome stabilization (10). We found that complete hypermethylation of the poly-CG molecule significantly increases its crookedness and flexibility, in quantitative agreement (table S3) with recent optical tweezers experiments reporting both an unusually high and a softening induced by hypermethylation in CGI (23). This could increase nucleosome affinity for a hypermethylated CGI (24).…”
supporting
confidence: 89%
“…Hypermethylation of CGI commonly induces gene silencing, and in some cases this has been attributed to nucleosome stabilization [10]. We found that complete hypermethylation of the poly-CG molecule significantly increases its crookedness and stretching flexibility, in quantitative agreement (Table S3 [ 15]) with recent optical tweezers experiments reporting both an unusually high S and a softening induced by hypermethylation in CGI [49]. This could increase nucleosome affinity for a hypermethylated CGI [56].…”
supporting
confidence: 88%
“…5a, where we compare the values of the effective stretch modulus of our benchmark dsRNA sequences with the ones reported in our previous work for their DNA counterparts. 21 Note that the poly-CG RNA duplex is exceptionally flexible, while in the DNA case experiments and simulations show that this sequence is highly stiff; 21,22,32 the poly-G DNA is very soft, 21,22 but one of the stiffest RNA sequences here studied; and the poly-A DNA is Fig. 3 Helical rise and helical twist standard deviation of all dinucleotides.…”
Section: Comparison Of Sequence Effects In Dsdna and Dsrnamentioning
confidence: 87%